Study of B → Kππγ decays. (July 2015) - Pilloni, Alessandro
Abstract: In b → sγ transitions, the Standard Model predicts that B 0 ( ) decays are related predominantly to the presence of right- (left-) handed photons in the final state. Therefore, the mixing-induced CP asymmetry in B → fCP γ decays is expected to be small, thus being any sizeable observed asymmetries due to New Physics. In this analysis, we extract information about the Kππ resonant structures by means of an amplitude analysis of the mKππ and mKπ spectra in B + → K + π − π + γ . The results are used, assuming isospin symmetry, to extract the mixing-induced CP parameters of the process B 0 → K 0 s ρ 0 γ from the time-dependent analysis of B 0 → K 0 s π + π − γ decays without an explicit amplitude analysis of this mode.